Tripterygium glycoside ameliorates neuroinflammation in a mouse model of Aβ25-35-induced Alzheimer's disease by inhibiting the phosphorylation of IκBα and p38. Issue 1 (1st January 2021) - Tang, Liang; Xiang, Qin; Xiang, Ju; Zhang, Yan; Li, Jianming
ABSTRACT: Alzheimer's disease (AD) is acommon neurodegenerative disease in the aged population. Tripterygium glycoside (TG) has been reported to protect the nervous system. However, the effect of TG on AD is still unknown. We aimed to explore the effect of TG on AD. Thirty-two C57BL/6J mice were randomly selected and assigned to the normal control,  AD model,  AD+donepezil,  and AD+TG groups. PC12 cells were assigned to the normal control,  AD cell model,  and AD+TG groups. The alterations in spatial memory and learning abilities of mice were measured by Morris water maze. Neuronal damage in mice was detected using Nissl staining. The expression levels of Aβ25-35,  p-Tau, and CD11b in brain tissues were detected using immunohistochemistry. The expression levels of IL-1β, TNF-α, NO, p-P38, P38, p-IκBα, Caspase1, COX2, and iNOS were measured using ELISAs, qRT–PCR, and western blotting.TG significantly improved the spatial memory and learning abilities of AD mice. Compared toAD model group, significantly lower expression levels of Aβ25-35,  p-Tau, and CD11b were observed in AD+TG group (p < 0.05). The neuron density significantly increased in AD+TG group (p < 0.05). Significantly lower expression levels of IL-1β, TNF-α, NO, caspase-1, COX2, iNOS, p-IκBα and p-P38 MAPK were detected in AD+TG group (p < 0.05). In summary, TG may exert aneuroprotective effect by suppressing the release of inflammatory factors and microglial activity and inhibiting the phosphorylation of IκBα and p38 MAPK. These findings may improve our understanding of the mechanism of TG intervention in AD.